Family business practices - Mumbai Archive Project Team (Jio Institute, 2024)
Saraswati Nakhva’s father, Narsu Vithoba Nakhva, was involved in the fishing business, while her mother, Padmabai, also worked as a fisherwoman. Narsu was an astute businessman who made a fortune in the lucrative pearl industry. Using these profits, NV Nakhva built the family residence.